Global cities : cinema, architecture, and urbanism in a digital age - Krause, Linda; Petro, Patrice, 1957- (New directions in international studies., 2003)
In this volume, scholars critique the growing body of literature on the current process broadly known as 'globalization'. The authors explore the complex geographies of modern cities and offer possible strategies for reclaiming a sense of place and community in these globalized urban settings.